A late Campanian large-sized elasmosaurid from James Ross Island with comments on the paleohistology of Antarctic elasmosaurids - O'gorman, José P. (2016)
Fil: O'gorman, Jose P. Consejo Nacional de Investigaciones Científicas y Técnicas. Buenos Aires, Argentina.